"Arise ye wretched of the earth" : the First International in a global perspective - Bensimon, Fabrice; Deluermoz, Quentin; Moisand, Jeanne, 1978- (Studies in global social history ;, 2018)
"Arise Ye Wretched of the Earth" provides a fresh account of the International Working Men's Association. Founded in London in 1864, the First International gathered trade unions, associations, co-operatives, and individual workers across Europe and the Americas.--